The night fairy - Schlitz, Laura Amy.; Barrett, Angela (Somerville, Mass. : Candlewick Press, 2010)
When Flory the night fairy's wings are accidentally broken and she cannot fly, she has to learn to do everything differently.
Wilson's Children, October 2010.
School Library Journal starred, April 2010.
Notable/Best Books (A.L.A.), January 2011.
Booklist starred, January 2010.
Publisher's Weekly, January 2010.
Horn Book, March 2010.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Fairies -- Fiction; Magic -- Fiction; Friendship -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction